The Intrinsic Link Between Food Allergy and Allergic Rhinitis : A Family Medicine Perspective on Atopic March and Persistent Nasal Symptoms - Hidayati, Nurul; Dwi Rahayu, Indriati; Rizki Fauzi, Muhammad (Family Medicine Department, Faculty of Medicine, Brawijaya University, 2025)
Allergic rhinitis (AR) is a prevalent chronic respiratory condition, yet its intricate connection with food allergy (FA) is often underappreciated in clinical practice. This paper examines the